2009
DOI: 10.1080/15332860903467649
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Media Richness into an Integrated Model of Consumers' Intentions to Use Online Stores in Their Purchase Process

Abstract: The objective of this study was to develop and empirically test a conceptual framework designed to explain consumers' intentions to use online stores in their purchase process. The proposed model integrates the variables that were identified from a literature review and introduces a new dimension: perceived media richness. An online survey was carried out and data from 749 consumers was collected and analyzed by applying structural equation modeling techniques. The results provide empirical support for media r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 96 publications
2
38
0
1
Order By: Relevance
“…Pengaruh media dalam menghasilkan komunikasi yang berkesan bergantung kepada ciriciri kekayaan yang dimilikinya (Daft & Lengel, 1986;Brunelle, 2009;Yang & Kankanhalli, 2014 komunikasi dengan media komunikasi (task-media fit). Konsep kesepadanan ini menjelaskan bahawa suatu tugas komunikasi itu perlu dikomunikasikan melalui media yang bertepatan dengan keperluan tugas komunikasi tersebut.…”
Section: Kekayaan Mediaunclassified
“…Pengaruh media dalam menghasilkan komunikasi yang berkesan bergantung kepada ciriciri kekayaan yang dimilikinya (Daft & Lengel, 1986;Brunelle, 2009;Yang & Kankanhalli, 2014 komunikasi dengan media komunikasi (task-media fit). Konsep kesepadanan ini menjelaskan bahawa suatu tugas komunikasi itu perlu dikomunikasikan melalui media yang bertepatan dengan keperluan tugas komunikasi tersebut.…”
Section: Kekayaan Mediaunclassified
“…Different lines of research have found richness and social presence to have significant effects on individuals' online behavior, including intention to use a website [1], online purchasing behavior [21], and even likelihood of deception in business email communication [12]. Hence, it is likely that phishing emails that vary in the amount of richness and presence cues are potentially more virulent-an issue that is particularly relevant given the increased sophistication of phishing emails.…”
Section: Introductionmentioning
confidence: 97%
“…Extending prior findings of Brunelle (2009), media richness including the varied communication channels in WeChat (such as active chatting with customer service), information exchange, emotional, or attitudinal communication has a powerful positive effect (β=0.514, t=8.909, p<0.001) on positive WOM. The strength of the direct media richness relationship with WOM is an indication of both the significance of mobile instant messaging as a brand communication tool and the high quality perception of the medium's messages.…”
Section: Media Richnessmentioning
confidence: 92%